INDIAN SCIENCE COMMUNITY historical and sociological studies. - Krishna, Venni ([S.l.] : ROUTLEDGE INDIA, 2024)
This book focuses on the historical and sociological dimensions of scientists working in laboratories in India, offering insights into the historical, sociological and policy factors that shape scientific pursuits. It illuminates the challenges, accomplishments and the evolving role of science in societal development. The author initiates a broader discourse on the interplay between scientific advancements, societal contexts and policy frameworks. The book fosters a deeper understanding of science's role in shaping India's social fabric and contributing to the global scientific dialogue. It also explores issues such as brain drain, science activism and the conflict between university- and government-run models of science. Lucid and topical, the book will be of considerable interest to both social and natural scientists, as well as the general academic community, including research students in science, technology, history, social history of science, science and technology studies and innovation policies.
Keywords: Research -- India -- History; Scientists -- India -- History; Science -- Social aspects -- India; SCIENCE / General; HISTORY / General; SCIENCE / History